2016
DOI: 10.1021/acssuschemeng.6b02244
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Metal/Acid Bifunctional Catalyst for the Conversion of Levulinic Acid to γ-Valerolactone

Abstract: A facile strategy was developed for the preparation of Ru nanoparticles supported on reduced graphene oxide (Ru/rGO) and its following functionalization with benzenesulfonic acid groups (Ru/rGO-S). The formation of a C–C bond between p-sulfophenyl and sp2 carbon of graphene can be unambiguously confirmed by XPS quantitative analysis. The two catalysts were used to catalyze the conversion of levulinic acid in aqueous phase, which is an important reaction during biorefinery. Not GC but HPLC was found to be the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 82 publications
0
39
0
Order By: Relevance
“…Compared to metal oxides, carbon supports show a stronger ability to stabilise both acid and metal sites because of their high hydrothermal stability and rich surface chemistry. Wang et al 79 developed a facile synthesis procedure for developing a graphene-supported Ru/SO 3 H bi-functional catalyst. In this process, Ru NPs are initially deposited on graphene, followed by its functionalisation with benzenesulfonic acid groups (Fig.…”
Section: Factors Affecting the Catalytic Activity Of Carbon Materialsmentioning
confidence: 99%
“…Compared to metal oxides, carbon supports show a stronger ability to stabilise both acid and metal sites because of their high hydrothermal stability and rich surface chemistry. Wang et al 79 developed a facile synthesis procedure for developing a graphene-supported Ru/SO 3 H bi-functional catalyst. In this process, Ru NPs are initially deposited on graphene, followed by its functionalisation with benzenesulfonic acid groups (Fig.…”
Section: Factors Affecting the Catalytic Activity Of Carbon Materialsmentioning
confidence: 99%
“…[5][6][7][8][9] Indeed, many reports exist into the catalytic conversion of LA using both homogeneous and heterogeneous noble and non-noble metal catalysts in liquid and vapor phase systems. [5][6][7][8][9][11][12][13][14][15][16][17][18] Among the various metals investigated, ruthenium appears to be the most active and selective metal for the conversion of LA to GVL, mainly due to its selective hydrogenation of carbonyl groups without altering other unsaturated functionalities. [11][12][13][14][15][16][17][18] However, traditional catalysts, such as commercial Ru/C, oen exhibit leaching of the ruthenium species through the formation of metal-carboxylate complexes with LA, which is likely caused by the weak acidity of LA (pK a ¼ 4.59), [19][20][21] results in a low catalytic activity and poor catalyst reusability.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the prerequisite for establishing an efficient ML to GVL conversion process is to develop high performance dual-functional solid catalysts containing metal nanoparticles and acidic sites to enhance the process efficiency (i.e., catalytic activity and selectivity) and process simplicity. 14,15 As a relative new class of crystalline ordered materials, metal-organic frameworks (MOFs), have attached signicant attention in several areas, in particular in the eld of catalysis, because of their controllable pores characteristics, large internal surface areas, and tunable chemical properties. [25][26][27] For example, the typical Zr-based MOF, UiO-66, is comprised of 12coordinated Zr 6 O 4 (OH) 4 clusters that are connected threedimensionally with terephthalic acid (BDC) linkers.…”
Section: Introductionmentioning
confidence: 99%
“…The satisfactory catalytic performance was proven to be attributed to the synergistic effect of acid sites on the SPES support and metal sites of the Ru nanoparticles. Reduced sulfonated graphene oxide supported Ru (Ru/rGO‐S) and reduced graphene oxide supported Ru (Ru/rGO) were fabricated to promote the hydrogenation of LA in aqueous solution by Wang et al . Contrasting experiments indicated that, although high hydrogenation performance was achieved at 50 °C under 2 MPa H 2 , the two catalysts exhibited different product selectivity.…”
Section: Bifunctional Catalytic Systems For Cascade Transformation Ofmentioning
confidence: 99%